The influence of social media influencer (SMI) and social influence on purchase intention among young consumers - Salehhuddin Sharipudin, Mohamad-Noor; Abdullah, Noor Aziah; Kai, Wan Foo; Hassim, Nurzihan (Taylor's University, 2023)
The implications of social media influencers (SMI) are more important than ever, specifically considering online purchasing has become a trend, more so as a result of the COVID-19 pandemic. In this respect, brands must employ social media influencers to attract customers, and who needs be more creative than traditional advertisers in generating purchase intent. In this context, our study employed the TEARS model (i.e. trustworthiness, expertise, attractiveness, respect, similarity) and the social influence theory to understand the predictors of consumer purchase intention. Our study aimed to examine: (1) the characteristics of social media influencers (i.e. trustworthiness, expertise, attractiveness, respect, similarity) as predictors of intention to purchase, and (2) the relationship between social influence and purchase intention among Gen Z. A total of 605 useable responses were collected. The study findings suggest that the four dimensions of the TEARS Model were established as predictors for purchase intention among Gen Z consumers with the exception of “Respect”. Besides, informational and normative influence were significant predictors of purchase intention. The study adds to the growing body on SMI impact by revealing the elements that influence Gen Z’s purchase intention. Our findings also shed further light on the understanding of the social influence theory and TEARS Model in a collectivist culture, particularly in the SMI context.